2023
DOI: 10.3390/plants12152766
|View full text |Cite
|
Sign up to set email alerts
|

Sand Burial, Rather than Salinity or Drought, Is the Main Stress That Limits the Germination Ability of Sophora alopecuroides L. Seed in the Desert Steppe of Yanchi, Ningxia, China

Abstract: Global change and environmental pollution have reawakened ecologists to the great threat of multi-stress interactions to different growth stages of plants. Sophora alopecuroides L., a dune plant, has been widely studied for its medicinal components and strong salinity tolerance. S. alopecuroides seeds, obtained from the desert steppe of Yanchi, Ningxia, China, were used to analyze the effects of sand burial, salinity, drought, and their interactions on seed germination (germination percentage, germination ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Researchers have noted that the environmental context is a key element in ecological studies, and when environmental stress factors become too extreme, situations may arise where no seedlings can survive, regardless of their ecological traits [ 18 ]. The latest research on the germination characteristics of S. alopecuroides seeds under different stress conditions found that sand burial is the most critical stress limiting seed germination [ 20 ]. A thick layer of sand can induce seed dormancy; however, even if seeds are successfully activated, seedlings might fail to germinate due to an inability to break through the sand layer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have noted that the environmental context is a key element in ecological studies, and when environmental stress factors become too extreme, situations may arise where no seedlings can survive, regardless of their ecological traits [ 18 ]. The latest research on the germination characteristics of S. alopecuroides seeds under different stress conditions found that sand burial is the most critical stress limiting seed germination [ 20 ]. A thick layer of sand can induce seed dormancy; however, even if seeds are successfully activated, seedlings might fail to germinate due to an inability to break through the sand layer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dominant among these are S. alopecuroides , Astragalus melilotoides , and Stipa caucasica subsp. glareosa [ 20 , 33 ]. Our experimental setup aimed to closely mimic these natural conditions, providing valuable insights into the adaptive mechanisms of S. alopecuroides in its native habitat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The germination parameters were determined with reference to the work of ( [8]; [12]; [18]; [19]; [20])…”
Section: Parameters Measuredmentioning
confidence: 99%